THE CONCEPT OF "DROP ZONING" OF AN UNMANNED OBJECT FROM UAV AS A WAY TO OVERCOME THE PROBLEM OF SIMULATION SICKNESS TO INCREASE THE EFFICIENCY OF FPV DRONE OPERATORS ACCORDINGLY - MAHEROVSKYI, DMYTRO; BOYKO , NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article describes the potential health problems that can arise within people who regularly use virtual reality tools and summarizes the problems that can interfere with the efficiency of the FPV drone operator who uses virtual reality as a basis. The factors causing health problems of operators are described, as well as the efficiency decrease of the drone operator depending on the degree of disorientation. In order to overcome the problems associated with long-term work in an FPV helmet for operators which are working on the task of dropping an object from a UAV, the concept of "UAV drop zoning" is proposed, which should give the UAV operator the opportunity to rest when it is known for sure that the UAV can perform the reset task without risk to others. The concept envisages the division of the "map" of the operational operation of the UAV into 3 zones: automatic drop, semi-automatic drop, and a no-drop zone. Strategies for the automated return of the UAV to the operator are described. This concept is aimed at improving the performance of the task due to the greater involvement of AI in the UAV control process, when the operator is not able to perform direct control, or control with the help of AI shows a more effective result.
Keywords: virtual reality; Head Mounted Displays; disorientation; work efficiency; UAV; drop zoning; automated drop from UAV; automated return to operator; healthcheck